Technical Note: Development of a phantom for dosimetric comparison of murine micro‐CT protocols with optically stimulated luminescent dosimeters. Issue 8 (20th July 2018) - Mendez, Claudia; Colpo, Nadine; Duzenli, Cheryl; Atwal, Parmveer; Gill, Brad
Abstract : Purpose: This work aims to evaluate the utility and accuracy of a mouse‐like phantom and optically stimulated luminescent dosimeters (OSLDs) in measuring dose delivered to the body and lung of mice undergoing micro‐CT imaging. Methods: A phantom with two cavities for NanoDot OSLDs (Landauer, Inc., Greenwood, IL) was designed and constructed using acrylic to model the mouse body and polyurethane foam to obtain an approximate lung tissue dose. The OSLD dose was compared to ion chamber measurements for the same imaging protocols delivered by a Siemens Inveon micro‐CT (Siemens Medical Solutions USA, Inc., Hoffman Estates, IL, USA). A whole body scan, using 80 kV, 0.5 mA and 0.5 mm of aluminum filter, was used to compare results to previously published data. Additionally, dose was measured for the whole body scan without the aluminum filter and two chest protocols (full and half rotation). Results: OSLD dose results agree with chamber measurements within 3%. Average OSLD measurements for the whole body scan without filter were 10.7 ± 0.7 cGy in the abdomen and 11.2 ± 0.7 cGy in the lung. For the full rotation chest protocol, the average dose measured in the lung was 65.8 ± 4.3 cGy and 60.2 ± 3.9 cGy in the abdomen. Average doses were 41.1 ± 2.7 cGy in the lung and 38.2 ± 2.5 cGy in the abdomen for the half rotation chest protocol. The OSLD measurements showed a coefficient of variation under 1.4%. A maximum rotational geometry under‐response of 0.86% with respect to exposure at normal incidence to the OSLD was measured. Conclusions: The doses measured were found to be comparable to other studies for the scanner configuration and protocols chosen. The phantom built for this study was found to give reproducible dose measurements with 4% uncertainty. In this way, a robust and convenient method is established for future dose assessment of micro‐CT protocols and interinstitutional comparisons.